Perioperative diabetes management of adult patients with diabetes: a best practice implementation project. Issue 1 (24th March 2022) - Chen, Tanghua; Kumaran, Suji; Vigh, Gia; Astorga, Cecilia; Beehan, Sean; Burrell, Maria; Deakin, Gail; Kernahan, Carmen; Lambrakis, Paul; Loader, Joanne; Ly, Nakim; Nguyen, Mark; et al.
ABSTRACT: Objectives: The objectives of this project were to conduct a retrospective healthcare records audit to determine the current compliance with evidence-based criteria regarding perioperative management of patients with diabetes; to identify barriers and facilitators to achieve compliance and develop strategies to address areas of non-compliance, and to implement evidence-based best practice recommendations for perioperative diabetic management and to assess the effectiveness of these strategies in improving compliance of perioperative diabetic management across five participating clinical areas in a large tertiary referral hospital. Introduction: Type 2 diabetes is a frequent co-morbidity among inpatients. It affects up to 20% of the general surgical population. Patients with diabetes undergoing surgery have a greater complication rate and length of hospital stay. Optimization of diabetes management of hospitalized patients will improve quality of care delivery, prevent postoperative complications and reduce length of stay and costs. However, there is limited knowledge and understanding of whether the current nursing practices concerning perioperative diabetic management meet the best practice recommendations outlined by JBI best practice criteria. Methods: A pre-post intervention healthcare record audit was conducted to examine compliance with nine best practice recommendations for perioperative diabetic management across five clinical areas. Following pre-intervention data analysis along with two focus group discussions, barriers to compliance with best practice criteria were identified and targeted strategies were used to address the issues. This project used the JBI Practice Application of Clinical Evidence System (PACES) and Getting Research into Practice (GRiP) tools. Results: Face to face education sessions and educational resources relating to perioperative diabetic management were delivered to nursing staff, which resulted in improved compliance for most of the audit criteria, with significant improvement in the areas of regular blood glucose level monitoring and nursing staff receiving education and training in the post-implementation analysis.